FRI0448 Evaluating health status of 620 patients with primary sjÖgren's syndrome using EQ-5D. (23rd January 2014) - Ng, W.-F.; Lendrem, D.; Mitchell, S.; Bowman, S.; Price, E.; Pease, C.; Emery, P.; Andrews, J.; Bombardieri, M.; Sutcliffe, N.; Pitzalis, C.; Lanyon, P.; et al.
Abstract : Background: EQ-5D is a standardised tool for measurement of health status and is an increasingly popular health-related quality of life instrument but has not been applied to patients with primary Sjögren's syndrome (PSS). EQ-5D provides a simple descriptive profile, a single index value for health status and a visual analogue score (VAS). The key advantages of EQ-5D are that the instrument is preference-based, easy to complete and the value sets can be easily converted to Quality Adjusted Life Years (QALY) to aid cost-utility analysis. Objectives: To evaluate the health status of a large cohort of patients with primary Sjogren's syndrome in the UK using EQ-5D. Methods: We evaluated the health status of 620 clinically well characterised PSS patients from the UK PSS registry (UKPSSR) who fulfil the American European Consensus Group classification criteria 2002. All data were collected prospectively using a standardised pro forma as previously described (1). Data were compared to the UK normative data provided by the EuroQoL. In addition, the relationship between the health status of PSS patients and various clinical and patient reported outcome measures of PSS were examined. Results: The proportion of PSS patients reporting any problem in mobility, self-care, usual activities, pain/discomfort & anxiety/depression were 42.4, 16.9, 56.7, 81.1 & 49.6 (%) respectively compared to 5.4, 1.6, 7.9, 30.2 & 15.7 (%) in the general UK population. The mean±SD VAS score was 59.9±21.2, compared to 81.3±16.8 for the general UK population. Univariate correlation analysis showed that EQ-5D VAS correlated with many clinical features of PSS but most strongly with fatigue, depression and pain with R values >0.5. Among the laboratory measures, only IgG levels, paraproteins and C3 correlated with EQ-5D VAS. Hierarchical cluster analysis showed that depression and fatigue are the most important determinants of variations in health status in this PSS cohort. Conclusions: To our knowledge, this is the first report on the health status of PSS patients using EQ-5D. PSS patients have significantly impaired health status compared to the UK general population. Depression and fatigue are the key determinants of health status in PSS. Our data adds to the growing body of evidence that effective management of fatigue is key to improving the health status of PSS patients. References: Ng WF et al, Rheumatology, 2011;50:32-9. Other UKPSSR collaborators: Moots R, Chadravarty K, Gendi N, Hamburger J, Richards A, Rauz S, Mulherin D, Kitas GD, Lloyd M, Moore L, Lawson C, Clunie G, Knight S, Symmons D, Carr A, Carrozzo M, Figuereido F, Macleod I, Tarn J, Foggo H, Mann S, Young-Min S, Field A, Kaye S, Mewar D, Akil M, Dasgupta B, Fedele S, Porter S, Li C, Hall F. Disclosure of Interest: None Declared